Dietary diversity and associated factors among adolescents in eastern Uganda: a cross-sectional study - Nathan Isabirye; Justine Nnakate Bukenya; Mary Nakafeero; Tonny Ssekamatte; David Guwatudde; Wafaie Fawzi (BMC, 2020)
Abstract Background Globally adolescents constitute over 16% but in SSA, they make up 23% of the population. While little is known about diets of these adolescents, rapid changes in physiological and social processes undergone require adequate diets. This study aimed to determine dietary diversity and associated factors among adolescents residing in the Iganga -Mayuge HDSS. Methods As part of the African Research, Implementation Science, and Education (ARISE) Network, we analysed collected data among 598 adolescents to assess the health status and adolescents' behaviour. Dietary diversity was scored using the 9 food group categories as per the Food and Agriculture Organization -WDDS. Crude and adjusted prevalence rate ratios were estimated using the modified Poisson regression model to identify associated factors. Results Among the participants, 45.3% had a low dietary diversity score. Proportions of adolescents who consumed from the different food categories over a 24-h period were; cereals/roots/tubers (99.7%), fats & oils (87.0%), spices & beverages (84.1%), sweets (77.1%), legumes (66.2%), other non-vitamin A-rich vegetables (53.8%), dark green leafy vegetables (42.3%), meat/poultry/fish (33.1%), dairy products (32.9%), eggs (11.2%), vitamin A-rich fruits and vegetables (33.4%) and other fruits (8.2%). Staying with a single parent or guardian, low socio-economic class, and dependency on home meals was associated with low dietary diversity. Conclusions Adolescents diets were low in diversity and characterised with low micronutrients source foods, but plenty of fats and oils. Interventions to address contributing factors to the burden ought to target the parenting contexts of the adolescents residing in rural eastern Uganda.